2021
DOI: 10.1103/physrevb.103.094414
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio calculations of the phase behavior and subsequent magnetostriction of Fe1xGax within the disordered local moment picture

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 57 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Fe in particular has a large local moment associated with it, and we expect the nature of predicted order in this material to be different between FM and PM states. Indeed, in an earlier work on Galfenol, a binary Fe-based alloy, we found that the nature of magnetic order significantly affected the nature of compositional order [77]. We only model the PM state in this work because the Curie temperature is around 120K [18,33,78], well below the temperatures at which these materials are annealed [60].…”
Section: Atomistic Modellingmentioning
confidence: 99%
“…Fe in particular has a large local moment associated with it, and we expect the nature of predicted order in this material to be different between FM and PM states. Indeed, in an earlier work on Galfenol, a binary Fe-based alloy, we found that the nature of magnetic order significantly affected the nature of compositional order [77]. We only model the PM state in this work because the Curie temperature is around 120K [18,33,78], well below the temperatures at which these materials are annealed [60].…”
Section: Atomistic Modellingmentioning
confidence: 99%
“…Both of these Fe-Si phases possess large miscibility and can tolerate significant nonstoichiometry. While both the α and α'' phases show BCC-like lattice symmetry, they differ in terms of the degree of chemical ordering (Marchant et al, 2021). Figure 2-7 shows schematics of the crystal structure for these two phases with chemical composition Fe1-xSix.…”
Section: Relevant Terminologies and Concepts In Magnetismmentioning
confidence: 99%
“…Figure 2-7. Schematics of crystal structures of non-stoichiometric A2-like, B2-like, and D03-like phases of composition Fe1-xSix, data are based on computational work reported by(Marchant et al, 2021) …”
mentioning
confidence: 99%